All Days 2005
DOI: 10.2523/iptc-10727-ms
|View full text |Cite
|
Sign up to set email alerts
|

Steam Injection in Fractured Carbonate Reservoirs: Starting a New Trend in EOR

Abstract: Significant volumes of heavy oil remain in fractured carbonate reservoirs worldwide. Some of these reservoirs are good candidates for the application of thermally assisted gas-oil-gravity-drainage (TA-GOGD), a novel EOR technique. Unlike a normal steam flood, the steam is used as a heating agent only to enhance the existing drive mechanisms. The elegance of TA-GOGD is that the fracture network is both used for the distribution of steam (heat) and the recovery of the oil. The number of wells can therefore be ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Al-Shizawi et al (1997) discussed the methods of heat monitoring in the same field for the same pilot project. Later studies on Qarn Alam showed the field application possibility and the physics of steam injection (Penney et al 2005;Shahin et al 2006;Penney et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Al-Shizawi et al (1997) discussed the methods of heat monitoring in the same field for the same pilot project. Later studies on Qarn Alam showed the field application possibility and the physics of steam injection (Penney et al 2005;Shahin et al 2006;Penney et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Out of these pilot tests, only the Qarn Alam project has been switched to a full field scale application (Rawnsley et al, 2005;Penney et al, 2005;Shahin et al, 2006). Babadagli and Bemani (2007) reported that the matrix drainage at relatively favorable laboratory conditions do not exceed 42% for challenging Qarn Alam cores containing ~3,000 cp dead oil.…”
Section: Introductionmentioning
confidence: 99%
“…Effective and economic oil recoveries from fractured reservoirs rely on better understanding of the flow in fractured network. Because of its importance, many different experimental (Kneafsy and Pruess, 1998;Chen, 2005;Bagci, 2004;Babadagli, 1995;Sumnu, 1995;Briggs et al, 1992;Dindoruk and Firoozabadi, 1995), theoretical (Rossen and Kumar, 1994;Katsuhiko, 1976, Bodin et al, 2003aReis, 1990), and numerical studies (Kolditz, 2001;Penney et al, 2005;Jensen et al, 1992;Tsang and Doughty, 2003;Kim, 2002;Nicholl et al, 2000) have examined multiphase fluid flow through a single fracture yet it still remains unclear what are the phase relative permeabilities. This is especially the case for heavy oil-water systems (Chen and Horne, 2006;Chen, 2005;and Diomampo, 2001).…”
Section: Introductionmentioning
confidence: 98%